Mutation of BAM2 rescues the sunn hypernodulation phenotype in Medicago truncatula, suggesting that a signaling pathway like CLV1/BAM in Arabidopsis affects nodule number - Thomas, Jacklyn; Frugoli, Julia (Frontiers in Plant Science, 2024)
The unique evolutionary adaptation of legumes for nitrogen-fixing symbiosis leading to nodulation is tightly regulated by the host plant. The autoregulation of nodulation (AON) pathway negatively regulates the number of nodules formed in response to the carbon/nitrogen metabolic status of the shoot and root by long distance signaling to and from the shoot and root. Central to AON signaling in the shoots of Medicago truncatula is SUNN, a leucine-rich-repeat receptor-like kinase with high sequence similarity with CLAVATA1 (CLV1), part of a class of receptors in Arabidopsis involved in regulating stem cell populations in the root and shoot. This class of receptors in Arabidopsis includes the BARELY ANY MERISTEM family which like CLV1 bind to CLE peptides and interact with CLV1 to regulate meristem development. M. truncatula contains five members of the BAM family, but only MtBAM1 and MtBAM2 are highly expressed in the nodules 48 hours after inoculation. Plants carry mutations in individual MtBAMs and several double BAM mutant combinations all displayed wild type nodule number phenotypes. However, Mtbam2 suppressed the sunn-5 hypernodulation phenotype and partially rescued the short root length phenotype of sunn-5 when present in a sunn-5 background. Grafting determined bam2 suppresses supernodulation from the roots, regardless of SUNN status of the root. Overexpression of MtBAM2 in wild type plants increases nodule numbers while overexpression of MtBAM2 in some sunn mutants rescues the hypernodulation phenotype, but not the hypernodulation phenotypes of AON mutants rdn1-2 or crn. Relative expression measurements of the nodule transcription factor MtWOX5 downstream of the putative bam2 sunn-5 complex revealed disruption of meristem signaling; while both bam2 and bam2 sunn-5 influence MtWOX5 expression, the expression changes are in different directions. We propose a genetic model, wherein the specific root interactions of BAM2/SUNN are critical for signaling in nodule meristem cell homeostasis in M. truncatula.